2020
DOI: 10.1002/cbdv.202000135
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Effects of Castanea henryi Aqueous Extracts on the Growth and Physiology of Brassica pekinensis and Zea mays

Abstract: The present study investigated the allelopathic effects of aqueous extracts of Castanea henryi litter on the growth and physiological responses of Brassica pekinensis and Zea mays. Treatment with high concentrations of leaf extract (0.05 g/ml for B. pekinensis and 0.10 g/ml for Z. mays) significantly increased malonaldehyde content and reduced seed germination, seedling growth, chlorophyll content, and the activity levels of antioxidant enzymes. These effects generally increased with increasing extract concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…20,21 However, although an increasing number of plants have been reported to exhibit allelopathic effects, most of them are still not clear about their allelopathic active constituents. 22,23 Similarly, A. argyi has been proven to be a strong allelopathic plant in our previous study, exhibiting herbicidal activity on both monocotyledonous and dicotyledonous weeds but with unknown active constituents. 13 The biological activity-guided separation method was adopted in this study to identify the key active compounds of A. argyi for allelopathy.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…20,21 However, although an increasing number of plants have been reported to exhibit allelopathic effects, most of them are still not clear about their allelopathic active constituents. 22,23 Similarly, A. argyi has been proven to be a strong allelopathic plant in our previous study, exhibiting herbicidal activity on both monocotyledonous and dicotyledonous weeds but with unknown active constituents. 13 The biological activity-guided separation method was adopted in this study to identify the key active compounds of A. argyi for allelopathy.…”
Section: Discussionmentioning
confidence: 82%
“…At present, the development of herbicides based on plant allelopathy has become a new means in the agroecosystem . Botanical herbicides developed based on allelochemicals are biodegradable after entering the environment, resulting in less pollution, conducive to the protection of agricultural production, and alleviating social health problems. , However, although an increasing number of plants have been reported to exhibit allelopathic effects, most of them are still not clear about their allelopathic active constituents. , Similarly, A. argyi has been proven to be a strong allelopathic plant in our previous study, exhibiting herbicidal activity on both monocotyledonous and dicotyledonous weeds but with unknown active constituents .…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the activity of enzymes of wheat and redroot pigweed (CAT, POD, APX, SOD) increased at different intercropping ratios. Allelochemicals in low concentrations affect receptor plants and stimulate them to improve the ability of their antioxidant enzyme activity to resist oxidative stress (Ming et al 2020). Previous research has confirmed the effect of allelopathic compounds on the enzymatic activity of CAT, SOD, APX, and POD in various plants, including Vigna unguiculata L., tomatoes, rice seedlings, Cucumis sativus L., and cucumber (Zuo et al 2012;Ahmad et al 2013;Siddique and Ismail 2013;Oyeniyi et al 2016;Ribeiro et al 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Studies about the allelopathic effect of L. camara were recorded in agricultural crops (Sahid and Sugau 1993;Ahmed et al 2007;Choyal and Sharma 2011;Gantayet et al 2014;Kar et al 2014;Mishra 2014;Tadele 2014;Enyew and Raja 2015;Rusdy and Ako 2017;Anwar et al 2018;Mawal and Patil 2019;Gautam et al 2021), bryophytes (Mishra 2014), forest crops (Hossain and Alam 2010) and communities (Gentle and Duggin 1997) and even to other weeds (Saxena 2000;Mishra 2014). In line with this, stimulatory effects of L. camara were also recorded in some agricultural crops (Tadele 2014;Enyew and Raja 2015;Ming et al 2020).…”
Section: Introductionmentioning
confidence: 87%